1982
DOI: 10.1063/1.444020
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction study and models of liquid ethane at 105 and 181 K

Abstract: The structure functions for liquid ethane at (1) T = 105 K and a molecular density ρ = 0.012 70 Å−3, and (2) T = 181 K and ρ = 0.011 10 Å−3 have been derived from new x-ray diffraction data. Treating the –CH3 group as a single scattering site, carbon–carbon (methyl–methyl) intermolecular pair distribution functions have been obtained from the structure function data by Fourier inversion. Using Monte Carlo simulation, no two-site exponential-6 interaction model, with sites at the observed C–C bond length, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Despite methane itself appearing spherically symmetric in X-ray experiments, intermolecular structural correlations revealed distributions indicative of tetrahedral molecular symmetry [15]. Similar studies have been reported for ethane [16], propane [17], n-butane [18], n-pentane [19], and so on. A common thread through these studies is that n-alkanes have increasing molecular flexibility with length and present richly complicated intermolecular structures.…”
Section: Introductionsupporting
confidence: 80%
“…Despite methane itself appearing spherically symmetric in X-ray experiments, intermolecular structural correlations revealed distributions indicative of tetrahedral molecular symmetry [15]. Similar studies have been reported for ethane [16], propane [17], n-butane [18], n-pentane [19], and so on. A common thread through these studies is that n-alkanes have increasing molecular flexibility with length and present richly complicated intermolecular structures.…”
Section: Introductionsupporting
confidence: 80%
“… Carbon–carbon pair correlation function g CC for liquid ethane at 105 K as calculated by AIREBO and the current model, and from experiment 31. [Color figure can be viewed in the online issue, which is available at www.interscience.wiley.com.]…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3. The structures of methane at 92 K and ethane at 181 K were used in fitting the AIREBO model parameters, and the model is able to reproduce the experimental pair correlation functions 48,49 quite accurately. The REBO model, on the other hand, generates liquids that are largely unstructured, with too many intermolecular pairs at close distances.…”
Section: B Hydrocarbonsmentioning
confidence: 99%